PENETAPAN KADAR FLAVONOID DAN AKTIVITAS ANTIOKSIDAN PADA EKSTRAK BATANG BROTOWALI (Tinospora crispa L.) DENGAN METODE CUPRAC - Asep Roni; Dewi Kurnia; Nurani Hafsyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Oxidative stress is damage caused by reactive oxygen species Compounds that can prevent oxidative stress are antioxidants. The brotowali plant (Tinospora crispa) has been used for the treatment of diabetes and hypertension. The brotowali plant contains secondary metabolites such as flavonoids. Flavonoids are known to be a class of compounds that have antioxidant activity. so it can be kind of solvent which is the most excellent in the test plant extract brotowali. Extraction was conducted by reflux-rise that use nhexane, ethyl acetate and ethanol 96%. Determination of antioxidant activity using them CUPRAC method. Determination of total flavonoid content using colorimetric aluminum chloride method with quercetin as standard. The results showed that the ethyl acetate extract sample had strong antioxidant activity compared to the extract sample with 96% ethanol and n-hexane. The EC50 value of the ethyl acetate extract was 53.637 g/mL. Extract with n-hexane solvent had the highest flavonoid content, namely 9,937 Ã‚Â± 0.009 gQE/100 g extract.